The efficacy and adverse events of delafloxacin in the treatment of acute bacterial infections: A systematic review and meta-analysis of randomized controlled trials - He, Rong; Lin, Fei; Yu, Bin; Qiu, Jingyue; Zheng, Lingli (Frontiers in Pharmacology, 2022)
This study aims to assess the clinical efficacy and adverse events of delafloxacin for the treatment of acute bacterial infections in adult patients through meta-analysis.The PubMed, Embase, Cochrane library, Web of Science, and Clinical Trial databases were searched till March 2022. All randomized controlled trials (RCTs) that evaluated delafloxacin and comparator antibiotics for treating acute bacterial infections in adult patients were included and analyzed. The clinical cure rate and microbiological eradication rate at the posttreatment visits were evaluated, whereas the secondary outcomes were defined as the risk of adverse events (AEs). A total of six RCTs involving 3019 patients with acute bacterial infection were included. There were no significant differences in clinical cure rate between delafloxacin and the comparators (OR = 1.06, 95% CI = 0.89–1.26). Additionally, a pooled analysis comprising six studies also indicated that delafloxacin had a microbiological eradication rate similar to comparators (OR = 1.33, 95% CI = 0.94–1.88). Any treatment-emergent adverse events (TEAEs) during the therapy showed no statistically significant differences between the delafloxacin and comparators (OR = 0.93, 95% CI = 0.80–1.08). The incidence of serious adverse events (SAEs) in therapy sessions was similar between delafloxacin and comparators (OR = 0.94, 95% CI = 0.67–1.32). The results of gastrointestinal disorders were (OR = 1.26, 95% CI = 1.01–1.56), nausea (OR = 0.77, 95% CI = 0.45–1.34), vomiting (OR = 1.00, 95% CI = 0.74–1.36) and diarrhea (OR = 2.10, 95% CI = 1.70–2.96), respectively. Our results showed that there was no statistical difference in the incidence of nausea and vomiting between delafloxacin and the comparators, but the incidence rate of diarrhea was higher in delafloxacin. It was further revealed that the incidence of neurological disorders was lower in the delafloxacin group. Thus, the clinical efficacy, microbiological eradication rate, and incidence of AEs of delafloxacin in the treatment of acute bacterial infections were similar to comparators, showing non-inferiority and potential as an alternative treatment agent.